A potential brain functional biomarker distinguishing patients with Crohn’s disease with different disease stages: a resting-state fMRI study - Huang, Mengting; Ma, Guina; Zou, Yan; Ma, Hui; Fan, Wenliang; Li, Xin; Zhu, Liangru; Han, Ping; Wang, Huan; Shi, Heshui (Frontiers in Neuroscience, 2024)
Background: The previous studies have demonstrated that patients with Crohn’s disease in remission (CD-R) have abnormal alterations in brain functional. However, whether brain function changes in patients with Crohn’s disease in activity (CD-A) and the relationship with CD-R are still unclear. In this study, we aimed to investigate whether the different levels of disease activity may differentially affect the brain function and to find the brain functional biomarker distinguishing patients with different disease stages by measuring the amplitude of low frequency fluctuations (ALFF). Methods: 121 patients with CD and 91 healthy controls (HCs) were recruited. The clinical and psychological assessment of participants were collected. The ALFF was compared among three groups by performing one-way analysis of variance, followed by a post hoc two-sample t-test. Differences among the groups were selected as seeds for functional connectivity analyses. We also investigated the correlation among clinical, psychological scores and ALFF. Hierarchical multiple regression analysis was used to examine the unique contribution of the ALFF characteristics of the disease stages. Results: There were widespread differences of ALFF values among the 3 groups, which included left frontal pole (FP_L), right supramarginal gyrus (SG_R), left angular gyrus (AG_L), right cingulate gyrus (CG_R), right intracalcarine cortex (IC_R), right parahippocampal gyrus (PG_R), right lingual gyrus (LG_R), right precuneous cortex (PC_R), left occipital fusiform gyrus (OFG_L). Significant brain regions showing the functional connections (FC) increased in FP_L, SG_R, PC_R and OFG_L between CD-A and HCs. Significant brain regions showing the FC increased in FP_L, SG_R, CG_R, PG_R, LG_R and OFG_L between CD-R and HCs. In binary logistic regression models, the LG_R (beta=5.138, P=0.031), PC_R (beta=1.876, P=0.002) and OFG_L (beta=3.937, P=0.044) was disease stages predictors. Conclusion: The results indicated the significance of the altered brain activity in the different disease stages of CD. Therefore, these findings present a potential identify neuroimaging-based brain functional biomarker in CD. Additionally, the study provides a better understanding of the pathophysiology of CD.